TEACHING ENGLISH VOCABULARY ONLINE: IS THE SCREEN A BARRIER? - Oksana Zabolotna; Liudmyla Zagoruiko; Ielyzaveta Panchenko; Yevhen Plotnikov (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2021)
This paper presents mixed-method research on teaching vocabulary online using a combination of quantitative (bibliometric approach) and qualitative (expert evaluation based on Delphi technique) methods to answer three research questions: Which tools in teaching language with technology have been described in research publications? Which tools are frequently addressed in EFL Methodology course in Ukrainian universities for teaching vocabulary online? Which tools and methods require more information for teaching vocabulary online? To answer the first research question, the authors have used a bibliometric approach to analyse the topic-related articles in the eight most relevant journals from the Scopus Database between 2011 and 2020. The authors have encountered few literature review articles tracking the developments in this research area and no articles using bibliometric methods or science maps. After finalising and structuring the bibliometric analysis data, the authors have used the Delphi method with the British Council experts who were involved in the New Generation School Teacher Project. The experts who are EFL Methodology teachers at 7 Ukrainian Universities have shared their experience in using the tools identified by the bibliometric analysis and listed the usability precedency and hurdles with their recommendations. The experts assisted in answering the research questions about the tools addressed in the EFL methodology course and those that require some consideration. As a result, the findings are collated and shared with EFL teachers, and they can gain valuable insights into the current state of the research and practice in this area. In the discussion part, the authors familiarise EFL teachers with the newest resources that provide information about the understudied areas.